Managing banana and citrus diseases: Proceedings of a regional workshop on disease management of banana and citrus throught the use of disease-free planting materials held in Davao city, Philippines, 14-16 October 1998 - Molina, A.B.; Roa, V.N.; Bay-Petersen, J.; Carpio, A.T.; Joven, J.E.A. (2000)
Citrus and banana are major cash crops for farmers in Southeast Asia. However both are experiencing dramatic declines in yield because of disease. The infections are so widespread that even nursery stock and parent trees generally used to replant diseased plantations are infected, and disease-free material must be sought from further afield. Advances in managing diseases of both Citrus and banana have involved developing new ways to efficiently produce and distribute uninfected seedlings, and of more sensitive ways to detect infections, which may frequently be latent or symptom-less. In the case of bananas disease-free material is obtained through tissue culture. For Citrus certified disease-free seedlings from disease-free nurseries are being promoted. In either case the lessons learnt in developing such integrated disease management programmes are valuable to farmers of all types of crop. The workshop on ”Managing banana and Citrus diseases”, jointly organised by INIBAP and the Food and Fertilizer Technology Center, based in Taiwan, brought together researchers at the forefront of the battle against banana and Citrus diseases in Southeast Asia. Their work on the epidemiology of viral diseases, their ecology, detection and methods of management for both bananas and Citrus is presented in this 164-page book. Results of studies on the epidemiology, characterization and management of bunchy top and viral streak viruses, in particular, are included. As are recommendations for research, development and policy resulting from this unique workshop.